Understanding food systems agriculture, food science, and nutrition in the United States - MacDonald, Ruth; Reitmeier, Cheryll (London Academic Press, 2017)
"Presenting the role and impact of technology, from production to processing and safety, to cultural and consumer behavior perspectives, the book also explores the link between food systems and the history of nutrients and diet patterns, and how these influence disease occurrence. Current topics of concern and debate, including the correlations between food systems and diet-related diseases, such as obesity and diabetes are explored, as are the history and current status of food insecurity and accessibility"--Provided by publisher.
Keywords: Food -- United States; Food supply -- United States; Farm produce -- United States; Agriculture -- United States; Nutrition -- United States